Targeted left ventricular lead positioning to the site of latest activation in cardiac resynchronization therapy: a systematic review and meta-analysis - Fyenbo, Daniel Benjamin; Bjerre, Henrik Laurits; Frausing, Maria Hee Jung Park; Stephansen, Charlotte; Sommer, Anders; Borgquist, Rasmus; Bakos, Zoltan; Glikson, Michael; Milman, Anat; Beinart, Roy; Kockova, Radka; Sedlacek, Kamil; et al. (Europace, 2023)
AIMS: Several studies have evaluated the use of electrically- or imaging-guided left ventricular (LV) lead placement in cardiac resynchronization therapy (CRT) recipients. We aimed to assess evidence for a guided strategy that targets LV lead position to the site of latest LV activation. METHODS AND RESULTS: A systematic review and meta-analysis was performed for randomized controlled trials (RCTs) until March 2023 that evaluated electrically- or imaging-guided LV lead positioning on clinical and echocardiographic outcomes. The primary endpoint was a composite of all-cause mortality and heart failure hospitalization, and secondary endpoints were quality of life, 6-min walk test (6MWT), QRS duration, LV end-systolic volume, and LV ejection fraction. We included eight RCTs that comprised 1323 patients. Six RCTs compared guided strategy (n = 638) to routine (n = 468), and two RCTs compared different guiding strategies head-to-head: electrically- (n = 111) vs. imaging-guided (n = 106). Compared to routine, a guided strategy did not significantly reduce the risk of the primary endpoint after 12-24 (RR 0.83, 95% CI 0.52-1.33) months. A guided strategy was associated with slight improvement in 6MWT distance after 6 months of follow-up of absolute 18 (95% CI 6-30) m between groups, but not in remaining secondary endpoints. None of the secondary endpoints differed between the guided strategies. CONCLUSION: In this study, a CRT implantation strategy that targets the latest LV activation did not improve survival or reduce heart failure hospitalizations.
Keywords: Hospitalization; hospitalizace; Heart Ventricles; echokardiografie; Echocardiography; lidé; Cardiac Resynchronization Therapy; srdeční resynchronizační terapie; Heart Failure; srdeční selhání; Humans; srdeční komory